THE IMPORTANCE OF THE PEDAGOGICAL EDUCATION SYSTEM FOR PARENTS IN FORMING THE EDUCATION OF STUDENTS (Scientific journal of the Fergana State University, 2024)
In the article, family members are connected to each other by unity of livelihood, mutual support and moral responsibility. The most important social tasks of the family, raising children, and effectively organizing the living conditions and free time of family members were discussed.